Trombe wall size-determination based on economic and thermal comfort viability. (1st November 2018) - Özdenefe, Murat; Atikol, Uğur; Rezaei, Marzieh
Highlights: Increasing Trombe Wall (TW) area reduces electricity consumption of ac system. In insulated new buildings, TW is economically feasible under N. Cyprus conditions. In no insulated new buildings, TW is feasible if its area is larger than 9 m 2 . TW area should be adjusted such that it will not cause uncomfortable environment. Abstract: The present work attempts to develop an approach for Trombe wall (TW) sizing through an integrative appraisal of energy consumption, economics and thermal comfort. There are many studies in the literature regarding TW sizing and its energy and economic viability. Nevertheless, they lack the separate energy and economics life cycle cost assessments of the TW based on the cases of building being new or existing. Besides, they leave out thermal comfort aspect and insulation status of the buildings. The current study is an effort to fill those gaps. The approach is tested in a case study, a hypothetical building's living room that is incorporated with a TW. A simple parametric study has been carried out by varying the TW area from 6.0 m 2 to 16.2 m 2 to perform energy and economic assessments. The results revealed that for thermally insulated new building where the room is only occupied in winter the construction of a TW is economically viable. If the building is not thermally insulated, the construction of a TW is only feasible if its area is greater than 9 m 2 . It is observed that the economic viability of the TW becomes better as its area increases. If the room is used in summer as well, there will be an extra cooling load due to the existence of the TW and economic feasibility is only achieved if there is insulation in the building. In uninsulated existing buildings, the construction of a TW is not economically feasible. The cumulative distribution frequency of various comfort parameters such as room temperature, relative humidity and CO2 concentration levels are also plotted for each feasible TW area for determining the best personal comfort level.